Associations of brominated flame retardants exposure with chronic obstructive pulmonary disease: A US population-based cross-sectional analysis - Lu Han; Qi Wang (Frontiers Media S.A., 2023)
BackgroundsWhether there existed an association between brominated flame retardants (BFRs) and chronic obstructive pulmonary disease (COPD) prevalence in humans is still a mystery.ObjectiveTo investigate the association between serum single or mixture BFRs and COPD prevalence.MethodsData of 7,591 participants from NHANES 2007-2016 was utilized. Serum BFRs, including PBDE-28, PBDE-47, PBDE-85, PBDE-99, PBDE-100, PBDE-154, PBDE-183, PBDE-209, and PBB-153 were enrolled. The survey-weighted generalized logistic regression model, restricted cubic splines (RCS), weighted quantile sum (WQS) regression, and quantile-based g-computation (QGC) analysis were performed.ResultsAfter adjustment for all confounding factors, log-transformed continuous serum PBDE-28 (OR: 1.43; 95% CI: 1.10-1.85; P = 0.01), PBDE-47 (OR: 1.39; 95% CI: 1.11-1.75; P = 0.005), PBDE-85 (OR: 1.31; 95% CI: 1.09-1.57; P = 0.005), PBDE-99 (OR: 1.27; 95% CI: 1.05-1.54; P = 0.02), PBDE-100 (OR: 1.33; 95% CI: 1.08-1.66; P = 0.01), PBDE-154 (OR: 1.29; 95% CI: 1.07-1.55; P = 0.01), PBDE-183 (OR: 1.31; 95% CI: 1.04-1.66; P = 0.02), and PBB-153 (OR: 1.25; 95% CI: 1.03-1.53; P = 0.03) were positively correlated with the prevalence of COPD. Restricted cubic splines curves displayed that PBDE-209 was significantly associated with CPOD in an inverted U-shape (P = 0.03). A significant interaction between being male and a high prevalence of COPD was observed for PBDE-28 (P for interaction <0.05), PBDE-47 (P for interaction <0.05), PBDE-85 (P for interaction <0.05), PBDE-99 (P for interaction <0.05), PBDE-100 (P for interaction <0.05), and PBB-153 (P for interaction < 0.05). Mixture BFRs exposure was positively associated with COPD prevalence in WQS regression (OR: 1.40; 95% CI: 1.14-1.72, P = 0.002) and in QGC analysis (OR: 1.49; 95% CI: 1.27-1.74, P < 0.001).ConclusionsOur study confirms that individual and mixture BFRs had positive associations with COPD, and further studies are required in larger-scale populations.